"Familial" versus "Sporadic" intellectual disability: contribution of common microdeletion and microduplication syndromes - Rafati Maryam; Seyyedaboutorabi Elaheh; Ghadirzadeh Mohammad R; Heshmati Yaser; Adibi Homeira; Keihanidoust Zarrintaj; Eshraghian Mohammad R; Javadi Gholam; Dastan Jila; Mosavi-Jarrahi Alireza; Hoseini Azadeh; Purhoseini Marzieh; et al. (Molecular Cytogenetics, 2012)
Abstract Background Interstitial Microdeletion and Microduplication syndromes have been proposed as a significant cause of sporadic intellectual disability (ID) but the role of such aberrations in familial ID has not yet been investigated. As the balanced chromosomal abnormalities commonly lead to the recurrent ID or multiple congenital anomalies, this study was designed to evaluate whether it was justified to investigate such aberrations in familial ID patients. Three hundred and twenty eight patients from 101 unrelated Iranian families with more than two ID patients in the first-degree relatives, have been investigated. Assessment of a panel of 21 common Microdeletion and Microduplication syndromes (CMMS) was carried out using Multiplex Ligation-Dependent Probe Amplification (MLPA) technique. Results Among the families studied, 27.7% had 4-12, 35.6% had 3 and 36.6% had 2 affected individuals in the first-degree relatives. An autosomal dominant inheritance of Williams-Beuren syndrome (WBS) was detected in a family with no clinical suspicion of WBS. The prevalence of CMMS was therefore,0.99%. Conclusion This is the first investigation of a panel of CMMS in a large sample set of "familial ID patients". The findings of this study showed the low prevalence of CMMSs in "familial ID" patients in spite of the significant contribution of such aberrations in "sporadic ID" which has a very useful practical impact by avoiding unnecessary diagnostic tests in "familial ID" patients.